EVALUATION OF THE COMBINATION OF BACTERIAL BIOFERTILIZER AND VERMICOMPOST IN THE AVAILABILITY OF N, P, K AND SOME OF PLANT PARAMETERS OF BEANS (PHASEOLUS VULGARIS L.) - & Abdul-Ratha, Al-Obaidi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
A field experiment was carried out at the Agricultural Research and Experiments (station A), which belong to the college of Agricultural Engineering Sciences/University of Baghdad with a silty loam soil by using Randomized Block Design with three replicates to evaluate the effect of using a combination of bacterial biofertilizer consist of Bacillus megaterium , Bacillus mucilagenosus and Rhizobium phaseoli with two levels of vermicompost (0 and 10 mcgh-1) on plant growth parameters of Green Beans and its yield and availability of N,P and K in soil under two levels of mineral fertilization (0% and 50%) of fertilizer recommendation in addition to using the full fertilizer recommendation treatment(100%) as a second control treatment. The results showed the significant superiority of the bacterial combination biofertilizer with (10 mcgh-1 ) vermicompost and 50% of mineral fertilizer compared with the treatment of full fertilizer recommendation in most of the growth and yield parameters of green beans, as the number of pods, nodules number and total yield were 150.00 plant pod-1 ,8.33 plant node-1and 71.48 mcg h-1respectively,whereas the soil content of a available NPK was 85.00,14.00 and 198.00 mcgh-1 in the same treatment above respectively in compare with the control(without any addition) treatment which its availability of NPK was (29.00,4.07 ,89.00)mgkg-1respectively.